Factors Associated with and Predictive Model for Resilience in Family Caregivers of Care-Dependent Adults - Belen Gutierrez-Baena; Ester Gilart; Carmen Romero-Grimaldi (Nursing Reports)
Background: Caring for dependent people is an intense task that leads family caregivers to suffer physical or mental pathologies. Resilience is a protective factor that makes an individual more resistant to adverse events. Some characteristics of the caregiver or the care provided predispose the caregiver to be less resilient. Knowing these characteristics will allow us to detect vulnerable caregivers. Aim: The aim of this study was to explore the factors associated with caregiver resilience and establish a predictive model, including the relationship between preparedness, burden, resilience, and anxiety. Materials and Methods: The study design was descriptive, observational, and cross-sectional, with purposive sampling. The sample included 172 family caregivers of care-dependent patients in Spain. Questionnaires were administered to assess caregiver resilience, anxiety, burden, and the preparedness of care-dependent patients. Correlation, univariate, and multiple linear regression analyses were performed to identify the factors associated with resilience. Results: We found that there is a correlation between resilience, preparation, and burden. Factors related to resilience include age, the caregiver’s health status, kinship, childcare, and state aid granted. Caregiver preparedness is the factor that most predicts caregiver resilience in our model. Caregivers with high levels of resilience also demonstrated high levels of preparedness and experienced less burden than those with low levels of resilience. Conclusions: These findings emphasize the relevance of improving the preparation of family caregivers to increase their resilience and, at the same time, the quality of care provided.